我用数学软件Matlab帮你做的
>> syms x y
>> z=exp(sin(2*x+3*y));
>> diff(z,x,1)
ans =
2*cos(2*x+3*y)*exp(sin(2*x+3*y))
>> diff(z,x,2)
ans =
-4*sin(2*x+3*y)*exp(sin(2*x+3*y))+4*cos(2*x+3*y)^2*exp(sin(2*x+3*y))
>> diff(z,x,3)
ans =
-8*cos(2*x+3*y)*exp(sin(2*x+3*y))-24*sin(2*x+3*y)*cos(2*x+3*y)*exp(sin(2*x+3*y))+8*cos(2*x+3*y)^3*exp(sin(2*x+3*y))
>> diff(z,y,1)
ans =
3*cos(2*x+3*y)*exp(sin(2*x+3*y))
>> diff(z,y,2)
ans =
-9*sin(2*x+3*y)*exp(sin(2*x+3*y))+9*cos(2*x+3*y)^2*exp(sin(2*x+3*y))
>> diff(z,y,3)
ans =
-27*cos(2*x+3*y)*exp(sin(2*x+3*y))-81*sin(2*x+3*y)*cos(2*x+3*y)*exp(sin(2*x+3*y))+27*cos(2*x+3*y)^3*exp(sin(2*x+3*y))